High efficiency analysis model for corrugated steel plate shear walls in modular steel construction. (November 2020) - Deng, En-Feng; Zong, Liang; Wang, Hai-Peng; Shi, Feng-Wei; Ding, Yang
Abstract: Modular steel construction has become increasingly popular in recent years, owing to its superiority in construction speed and quality. Corrugated steel plates are commonly used as the surface enclosure and lateral force resisting component for the module unit. However, establishing precise finite element models considering all geometric characteristics of corrugated steel plate shear walls (CSPSWs) is complex, especially for walls that include openings. Consequently, it is necessary to develop a high efficiency analysis model (HEAM) for CSPSWs to perform the dynamic structural analysis. In this paper, the skeleton curve and hysteretic regulation of CSPSWs were proposed, and universal formulas were deduced to determine the hysteretic model of CSPSWs. In addition, equivalent cross braces were proposed to simulate the seismic performance of CSPSWs, and the design parameters of the equivalent cross braces were determined according to the equivalence of the load bearing capacity and mass. The accuracy and reasonability of the HEAM were validated against available cyclic test data on CSPSWs. Furthermore, the HEAM was verified at the structural level by comparing the dynamic response of the HEAM with the precise analysis model (PAM) for a six-story and a 20-story modular container structure, respectively. The comparisons demonstrated that the HEAM was capable of providing a conservative prediction of the dynamic response of CSPSWs under earthquake compared to the PAM. The HEAM developed in this study was helpful in improving the analysis efficiency of CSPSWs and can be adopted for the nonlinear seismic analysis of modular steel construction. Highlights: A high efficiency analysis model (HEAM) for CSPSWs was developed and verified. The equivalent cross braces were proposed to simulate the seismic behavior of CSPSWs. Skeleton curve and hysteretic regulation for CSPSWs were proposed and verified. The HEAM can be used for dynamic analysis of CSPSWs both with and without openings.